The Asymmetric Effect of Trade Openness on Output Volatility: Empirical Evidence from Ethiopia - Degu, Adisu Abebaw; Bekele, Dagim Tadesse; Ayenew, Belesity Bekalu; Abate, Chala Amante (Journal of Developing Economies, 2023)
A better understanding of the effect openness on volatility can lead to more effective government policy that addresses the adverse outcomes of volatility. By using NARDL model, Hodrick-Prescott (HP) filter, and annual time-series data from the period 1981 to 2020, this study examined the effect of openness on output volatility in Ethiopia. From the NARDL bound test, the research find a long-run cointegration between output volatility, agricultural output, trade openness, lending rate, and money supply. We also found a long-run negative asymmetric effect, and short-run negative symmetric effect of openness on volatility”suggesting this open trading activity has a relationship that can reduce output volatility in Ethiopia. This possibility shows Ethiopia would benefit from international trade and openness reduces the adverse effects of volatility. Besides, we confirmed the positive asymmetric effect of agricultural output both in the long run and short run. The lending rate, that represents the cost of borrowing, has a positive effect on output volatility. The long-run and short-run coefficients of money supply have a negative and significant effect on output volatility.